Uji Aktivitas Antiinflamasi Ekstrak Daun Benalu Jeruk (Dendrophthoe glabrescens (Blakely) Barlow) terhadap Mencit (Mus musculus) yang Diinduksi Karagenan - Udayani, Ni Nyoman Wahyu; Mahendra, I Putu Aldy; Widiasriani, Ida Ayu Putu; Mahardika, I Made Agus; Wardani, I Gusti Agung Ayu Kusuma (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Inflammation is a natural defense mechanism of the body against injury or disease; however, excessive inflammation can lead to various chronic conditions. Prolonged use of synthetic anti-inflammatory drugs is associated with adverse effects, creating a need for safer natural alternatives. One such candidate is the citrus benalu leaf (Dendrophthoe glabrescens (Blakely) Barlow), a parasitic plant rich in flavonoids, saponins, and tannins. This study aimed to evaluate the anti-inflammatory activity of ethanol extract from citrus benalu leaves in carrageenan-induced mice. A laboratory experimental design using a Randomized Pre- and Post-Test Control Group approach was employed with 25 mice divided into five groups: negative control (CMC-Na 0.5%), positive control (sodium diclofenac), and three treatment groups receiving citrus benalu leaf extract at doses of 100, 200, and 400 mg/kgBW, respectively. The extract was administered orally 30 minutes after carrageenan induction, and paw edema was measured every 30 minutes for 180 minutes. One-way ANOVA revealed significant differences among groups, and LSD post hoc analysis indicated that all treatment groups differed significantly from the negative control (p < 0.05) but not from the positive control (p > 0.05). The 400 mg/kgBW dose demonstrated the greatest efficacy, reducing paw edema to 3.08%. These findings suggest that citrus benalu leaf extract has promising potential as a natural anti-inflammatory agent, offering an alternative to synthetic drugs with fewer side effects.